2000
DOI: 10.1016/s0896-6273(00)81203-9
|View full text |Cite
|
Sign up to set email alerts
|

Selective Depression of Low–Release Probability Excitatory Synapses by Sodium Channel Blockers

Abstract: Sodium channels (NaChs) play a central role in action potential generation and are uniquely poised to influence the efficacy of transmitter release. We evaluated the effect of partial NaCh blockade on two aspects of synaptic efficacy First, we evaluated whether NaCh blockade accounts for the ability of certain drugs to selectively depress glutamate release. Second, we evaluated the contribution of NaChs to intraneuronal variability in glutamate release probability (p(r)). The antiglutamate drug riluzole nearly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
101
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(113 citation statements)
references
References 35 publications
11
101
1
Order By: Relevance
“…We found that evoked GABAergic IPSCs displayed no waveform differences when grown on either ϩastrocyte or Ϫas-trocyte microcultures ( Fig. 2A, gray bars) and were indistinguishable from IPSCs from previous work (Bekkers and Stevens, 1991;Mennerick and Zorumski, 1995;Prakriya and Mennerick, 2000;Vecchia et al, 2014).…”
Section: Postsynaptic Currents Of Glutamatergic But Not Gabaergic Nsupporting
confidence: 61%
“…We found that evoked GABAergic IPSCs displayed no waveform differences when grown on either ϩastrocyte or Ϫas-trocyte microcultures ( Fig. 2A, gray bars) and were indistinguishable from IPSCs from previous work (Bekkers and Stevens, 1991;Mennerick and Zorumski, 1995;Prakriya and Mennerick, 2000;Vecchia et al, 2014).…”
Section: Postsynaptic Currents Of Glutamatergic But Not Gabaergic Nsupporting
confidence: 61%
“…The marked increase in the Gln/Glu ratio at day 2 of riluzole treatment was unexpected, given previous in vitro findings that riluzole decreases presynaptic glutamate release (Doble et al, 1992;Martin et al, 1993;Prakriya and Mennerick, 2000;Wang et al, 2004). However, animal studies provide some support for our finding.…”
Section: Riluzole and Glutamatergic Neurotransmissionsupporting
confidence: 59%
“…An alteration in the firing threshold for somatic or extracellular activation that involves the Na/K-ATPase could contribute to short-term depression at these synapses (Munoz-Cuevas et al 2004). A failure of an action potential to invade some axonal branches may contribute to depression in cultured hippocampal cells (Brody and Yue 2000;Prakriya and Mennerick 2000), but action potential invasion of axons is generally reliable in more intact tissue (Cox et al 2000;Kreitzer and Regehr 2001;Brenowitz and Regehr 2007).…”
Section: Inactivation Of Calcium Channels and Other Mechanisms Of Depmentioning
confidence: 99%